Defensive insect symbiont leads to cascading extinctions and community collapse. (10th June 2016) - Sanders, Dirk; Kehoe, Rachel; van Veen, FJ Frank; McLean, Ailsa; Godfray, H. Charles J.; Dicke, Marcel; Gols, Rieta; Frago, Enric
Abstract: Animals often engage in mutualistic associations with microorganisms that protect them from predation, parasitism or pathogen infection. Studies of these interactions in insects have mostly focussed on the direct effects of symbiont infection on natural enemies without studying community‐wide effects. Here, we explore the effect of a defensive symbiont on population dynamics and species extinctions in an experimental community composed of three aphid species and their associated specialist parasitoids. We found that introducing a bacterial symbiont with a protective (but not a non‐protective) phenotype into one aphid species led to it being able to escape from its natural enemy and increase in density. This changed the relative density of the three aphid species which resulted in the extinction of the two other parasitoid species. Our results show that defensive symbionts can cause extinction cascades in experimental communities and so may play a significant role in the stability of consumer‐herbivore communities in the field.